(untitled) (Altre Modernità, 2025)
In recent years, Elena Ferrante has gained significant popularity in the People’s Republic of China, where her Neapolitan Novels resonate with Chinese readers for their deep exploration of intimate relationships, female friendship, identity, and the challenges of growing up in a rapidly changing environment. Reinforcing images of “Italianness” and fostering intercultural dialogue, Ferrante’s novels continue to inspire book clubs, literary discussions, and cultural analyses, including on TV. On March 9, 2023, the Neapolitan Novels were featured on China Central Television (CCTV) in Reading (Dushu 读书), a program of CCTV-10, the channel dedicated to science and education. Building on previous studies on the Chinese circulation and reception of the tetralogy, this paper adopts a qualitative, discourse-oriented approach to examine its TV-mediated interpretation. The analysis begins by exploring Ferrante’s transnational reach and the Chinese dissemination of the Neapolitan Novels, and then outlines the role of cultural and educational programs on Chinese television before turning to the case study of Reading’s episode on Ferrante. The exploration focuses on how the show presents the novels through an emotionally resonant lens, framing female friendship as a universally accessible and morally instructive theme. Particular attention is given to the visual and narrative strategies used to integrate Ferrante’s tetralogy into China’s cultural discourse. Through this case study, the paper aims to offer a deeper understanding of the popularization of the Neapolitan Novels in China, while contributing to broader debates on the role of national media in shaping the cultural positioning of foreign literature.